Life Chances, Choices and Identity: Single Mothers in Post-Secondary Education - Parsons, Janice E. (Atlantis)

(untitled) (Mount Saint Vincent University, 2008)
A qualitative study of classed and gendered identities of single mother university students on welfare is reported. The women's negotiations of these complex identities are germane to their educational and economic success, health and well-being. Habitus is used to explore trajectories and dispositions reflecting the women's life chances and choices.